INOVASI SISTEMIK PEMBIAYAAN PERJALANAN UMRAH MELALUI AMITRA SYARIAH FINANCING (STUDI KASUS PT. WAKAFA ZAIN ABUL HUSNA) - Lubis, Mukhlis (Prodi Hukum Ekonomi Syari'ah STAIN Mandailing Natal, 2020)
Umrah travel package take costs that are not small because of influenced by the cost of airline tickets, star hotels and food and documents. Some people need a solution really realize their desire to carry out umrah. One solution offered by Amitra Syariah Financing in the form of financial bailout for prospective pilgrims when they are willing to have Umroh through PT. Wakain Zain Abul Husna. This innovation is a system that solves the financial problems of Muslims. This system innovation focused on the payment system, cooperation with Islamic banking, travel agents, customers, fatwa of National Sharia Board-Indonesian Council of Ulama (DSN-MUI) and other stakeholders and the system as a human creation. This system innovation raises pros and contras, will it be a way out of financial problems for Umrah or become a financial problem after having Umrah? The role of ethics in doing business occurs in this system innovation.